Study of Relationship between the slice thickness vs. image Quality in Abdomen CT Examinations with fixed another parameter - Fathi A. Awushah; Rajab.B. Yousef (Surman Journal of Science and Technology, 2024)
High-quality and detailed computed tomography (CT) images are essential for accurate diagnosis. Factors such as image noise and slice thickness affect image quality. This study aimed to determine the optimal slice thickness that minimizes image noise while maintaining adequate diagnostic information using multi-slice CT (MSCT). To investigate the effect of slice thickness on noise and contrast in images, four patients who underwent abdominal CT scans were consecutively studied. They were scanned at two levels of slice thickness: 2 mm and 5 mm, and 3 mm and 5 mm, respectively other parameter are the same. Then, quantitative analysis was performed. The study showed that thin slice thickness led to: Reduced image noise Increased contrast Improved detection Therefore, a balance should be considered between changing slice thickness and diagnostic content and image noise., slice thickness of 2 mm was identified as an optimal choice to minimize image noise and achieve better and more accurate detection using a single-source head CT protocol. The study also revealed that image noise tends to increase with increasing slice thickness.